Pharyngeal perforation secondary to electrical shock from a Taser gun. Issue 6 (22nd May 2008) - Al-Jarabah, M; Coulston, J; Hewin, D
Abstract : The case history is presented of a patient who developed pharyngeal perforation following the use of a Taser electroshock gun. This complication has not previously been reported.